2008
DOI: 10.1111/j.1541-4337.2007.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of Physics‐Based Models in the Design of Food Products, Processes, and Equipment

Abstract: This article is part of a collection entitled "Models for Safety, Quality, and Competitiveness of the Food Processing Sector," published in Comprehensive Reviews in Food Science and Food Safety. It has been peer-reviewed and was written as a follow-up of a pre-IFT workshop, partially funded by the USDA NRI grant 2005-35503-16208.ABSTRACT: Modeling, in particular physics-based modeling, can be an important tool to food product, process, and equipment designers by reducing the amount of experimentation (thus red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 29 publications
0
42
0
5
Order By: Relevance
“…However, optimization of newer thermal processing technologies, such as microwave heating, is more challenging because it requires more sophisticated mathematical models and computer simulations with more complicated heating patterns that can be difficult to validate (Tang 2015;Datta 2008). This type of complex simulation and numerical modeling for microwave heating systems was not even possible until the late 1980s; now calculation intensive models are possible because of advances in computer technology and increased computing power (Datta and Anantheswaran 2001;Chandrasekaran et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…However, optimization of newer thermal processing technologies, such as microwave heating, is more challenging because it requires more sophisticated mathematical models and computer simulations with more complicated heating patterns that can be difficult to validate (Tang 2015;Datta 2008). This type of complex simulation and numerical modeling for microwave heating systems was not even possible until the late 1980s; now calculation intensive models are possible because of advances in computer technology and increased computing power (Datta and Anantheswaran 2001;Chandrasekaran et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Mathematical modeling serves to improve our understanding of the phenomena, and, more importantly, for designing and optimizing food processes (Datta, 2008;Feyissa et al, 2012;Ho et al, 2013;Perrot et al, 2011;Torrez Irigoyen et al, 2014) in a virtual way by simulation. As we demonstrated here for controlled atmosphere storage of pear fruit, such an approach must account for the complex and variable structure, shape, size and physiological properties of the food through stochastic simulation techniques (Hertog et al, 2007;Rogge et al, 2013;Scheerlinck et al, 2001;Serment-Moreno et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changes in formulation and/or the conditions under which the RSM was derived are not possible. It has been previously indicated that physics-based modeling can be an important tool for food product, process, and equipment designers by reducing the amount of experimentation and providing a level of insight that is often not achievable experimentally (Datta, 2008). Hence, RSM should probably be restricted to a handful of practical and limited cases.…”
Section: Modelingmentioning
confidence: 97%